Responsible Governance in Containing the Spread of COVID-19 in a Developing State - Mukherjee, Debarshi; Chakraborty, Subhayan; Bhadra, Subhasis; Hasan, Khandakar Kamrul; Jena, Lokesh Kumar; Debnath, Ranjit (Journal of Education Culture and Society, 2022)
Aim. The study aims to evaluate the government policy implementation in tackling the global pandemic and framing universal policies for responsible governance. It also measures the impact of training interventions and non-training implications in containing the spread of COVID-19 at the grassroots level.Methods. The samples were drawn empirically from pathological tests conducted over 23 weeks to precisely examine the success of the State Government's approach in lowering COVID-19 mortality and spread. Through trend analysis, the outcome has been predicted. The study establishes a link between acknowledged ideas and government practices, providing insight into how relevant the implementation of planned state-craft programs is.Results. The findings indicated that government-imposed policies account for timely pandemic containment, and even a tiny developing state lacking advanced medical facilities and technology can set an example in combating the epidemic.Conclusions. The temporal analysis is based on the inputs acquired from government publications and other sources, allowing us to assess policy initiatives that encompass training interventions and non-training implications as prioritized by the State Government. The paper shows that a good emergency preparedness and response system is needed to prevent huge losses in any sector. This includes the already-struggling health sector, which India needs to put first to avoid more tragedies.